Revisiting 'resilience' in light of racism, 'othering' and resistance. (July 2022) - Sims-Schouten, Wendy; Gilbert, Patricia
In this commentary the authors analyse how the concept of resilience can be and has been applied to Black, Asian and minority ethnic families and communities in ways that are biased, stigmatising and pathologising. They argue that current definitions of resilience need to be redefined and reconceptualised, particularly in settings dominated by White middle-class voices that define what 'positive emotions', 'successful traits' and 'coping mechanisms' entail. Here, through racism and flawed perceptions and interpretations of resilience and 'othering', members from ethnic minority communities are defined as in need of resilience support, whilst at the same time their experience of structural racism, e.g., in relation to mental health support, social/health care practices and school exclusions, is being erased. Instead, the authors argue that resilience can also mean 'resistance', i.e., resisting bad treatment and racism, as well as reflecting agency, identity and ownership of one's own life and choices within this. Reframing resilience thus means taking account of multifaceted and interactive effects of personal, material, institutional and political factors that impact on behaviour, wellbeing and resilience, as well as acknowledging that the way in which 'behaviour' is received is by default flawed, if this is largely informed by an oppressive White middle-class viewpoint.